Implementation Quality Level of Health Public Service Policy in Banten Province Local Hospital (RSUD) - Rahayuningsih, Yunia; Anggraini, Yusniah; Listyaningsih, Listyaningsih (Jurnal Bina Praja, 2018)
Public Hospital (RSUD) of Banten Province, as the Province Referral Hospital, is required to always improve the quality of service in every line to achieve excellent service and also to give satisfaction to the public. Public satisfaction is one of the goals that must be considered by Banten Province Public Hospital because one indicator in achieving the success of health services is the achievement of public satisfaction. On this basis, it is important for the Banten Province Public Hospital to make measurements on the public satisfaction. Related to that, this study aims to find out the quality of public services in Banten Province Public Hospital, which is measured through Public Satisfaction Index (IKM), including problems faced in the provision of public health services in Banten Province Public Hospital. The research method used is survey method with a quantitative descriptive approach. The data is obtained through questionnaires, observations, and documentation. The sample size is 100 people, which is determined by quota sampling technique. The results showed that quantitatively, the quality of public service in Banten Province Public Hospital based on Public Satisfaction Index reached 75.71, which is qualitatively categorized as good. Although it has been categorized as good, of the ten elements assessed, there are some elements that need to get serious attention, namely elements of information, complaint handling, the behavior of service personnel, service time, and supporting elements.